The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2013
DOI: 10.1111/j.1745-493x.2012.03275.x
|View full text |Cite
|
Sign up to set email alerts
|

Supplier Integration and NPD Outcomes: Conditional Moderation Effects of Modular Design Competence

Abstract: Integrating suppliers into new product development (NPD) projects offers manufacturers the potential for substantial improvements in the new product being designed. However, it also creates significant inter‐organizational integration diseconomies that can negatively affect the manufacturing cost and performance of the designed product. We propose that these diseconomies can be reduced to the extent that the manufacturer is able to design modular products — i.e., it has a modular design competence (MDC). We al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
96
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 95 publications
(102 citation statements)
references
References 139 publications
5
96
0
1
Order By: Relevance
“…In this study, we proposed and confirmed a contextual effect of supply base R & D on the link between a focal firm's own R & D, commercialization and its performance. These results are consistent with a cooperative view of ACAP (Malhotra et al., ) as well as results reported in the supplier integration literature (Koufteros et al., ; Narasimhan et al., ; Perols et al., ; Salvador & Villena, ). Researchers have found that a focal firm's supply base contributes to the ability of the focal firm to enhance its own R & D and commercialization choices.…”
Section: Discussionsupporting
confidence: 91%
“…In this study, we proposed and confirmed a contextual effect of supply base R & D on the link between a focal firm's own R & D, commercialization and its performance. These results are consistent with a cooperative view of ACAP (Malhotra et al., ) as well as results reported in the supplier integration literature (Koufteros et al., ; Narasimhan et al., ; Perols et al., ; Salvador & Villena, ). Researchers have found that a focal firm's supply base contributes to the ability of the focal firm to enhance its own R & D and commercialization choices.…”
Section: Discussionsupporting
confidence: 91%
“…These activities assimilate information acquired from customers and suppliers, allowing for the inclusion of superior technologies and materials in the early stages of product design (Lakemond, Echtelt & Wynstra, 2001;Petersen, Handfield & Ragatz, 2005;Song & di Benedetto, 2008;Yan & Dooley, 2014). Thus, it is insufficient to simply acquire information, but rather benefits emerge through leveraging suppliers' expertise in a cooperative fashion (Morris & Carter, 2005;Nellore, 2001;Salvador & Villena, 2013;Tan & Tracey, 2007;Tracey, 2004). This infers the importance of information assimilation during NPD as a dimension of AC (Parker, Zsidisin & Ragatz, 2008;Rogers, Lambert & Knemeyer, 2004).…”
Section: Responsive Strategy Absorptive Capacity and Firm Performancementioning
confidence: 99%
“…Importantly, foregoing research has not examined possible mediators of supply chain intelligence that might explain these mixed findings. The influence of supply chain intelligence integration is therefore in need of further study (Salvador & Villena, 2013;Wowak, Craighead, Ketchen, & Hult, 2013), especially pertaining to its influence on the specific outcome of new product launch success.…”
Section: Introductionmentioning
confidence: 99%